Phenotypic Properties Of Collagen In Dentinogenesis Imperfecta Associated With Osteogenesis Imperfecta - Salwa Ibrahim; Adam P Strange; Sebastian Aguayo; Albatool Shinawi; Nabilah Harith; Nurjehan Mohamed-Ibrahim; Samera Siddiqui; Susan Parekh; Laurent Bozec (Dovepress, 2024)
Indexed by ERA